Invasive Insects (Adventive Pest Insects) in Florida - J. Howard Frank; Michael C. Thomas (EDIS)
The term 'invasive species' is defined as 'non-native species which threaten ecosystems, habitats, or species' by the European Environment Agency (2004). It is widely used by the news media and it has become a bureaucratese expression. This is the definition we accept here, except that for several reasons we prefer the word adventive (meaning they arrived) to non-native. So, 'invasive insects' in Florida are by definition a subset (those that are pests) of the species that have arrived from abroad (adventive species = non-native species = nonindigenous species). We need to know which insect species are adventive and, of those, which are pests. This document is ENY-827, one of a series of the Entomology & Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: May 2004.